A descriptive analysis of rabies post‐exposure prophylaxis data: 2013, Ontario, Canada. (13th October 2017) - Middleton, D.; Edwin, J. J.; Johnson, K. O.; Warshawsky, B. F.
Summary: By 2013, the number of confirmed rabid animals in Ontario had decreased to unprecedented low numbers, yet the expected decrease in the number of courses of rabies post‐exposure prophylaxis (RPEP) administered did not occur consistent with the decrease in animal rabies cases (Figure1 ). This prompted a review of the reasons that RPEP was administered in Ontario. This study provides a descriptive analysis of the exposure incidents resulting in RPEP administration in Ontario during 2013 using data obtained from the integrated Public Health Information System, a Web‐based disease surveillance system. Findings from the study revealed that the number of RPEP courses administered could be reduced, without increased risk of rabies, through the following strategies: (i) Education and resources for public health staff and healthcare providers who assess animal exposures to improve interpretation of guidelines for RPEP administration. (ii) Refinement of guidelines for public health staff and healthcare providers to ensure that they support detailed consideration of the circumstances of the exposure in order to assist with the risk assessment. Guidelines should also support completion of a risk assessment when exposures to skunks, foxes, raccoons and other wild carnivores are provoked by the victim, as opposed to automatically providing RPEP as recommended by current guidelines. (iii) Public education strategies to prevent exposures to animals (e.g., do not touch unattended animals, bat proofing your house, proper removal of bats from the house). (iv) Defining the criteria to declare a jurisdiction rabies‐free. (v) Exploring strategies to improve surveillance for rabid animals.